Awakening Indigenous Knowledge: Perspectives and Experiences of Indigenous Early Childhood Education Diploma Students - Stagg-Peterson, Shelley; Huston, Lori; Ings, Eugema; Mason, Brenda; Falcigno, Kim (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2021)
We draw on a focus group discussion amongst four Indigenous northern Ontario early childhood educators (ECEs) from an Indigenous postsecondary institution’s ECE diploma program, to show the important contributions of programs offered by Indigenous postsecondary education institutes to Indigenous cultural revitalization. We are the Indigenous Elder, two instructors, and senior administrator of the program, as well as a non-Indigenous university professor. We argue for Indigenous community-generated curricula that embody local Indigenous cultural knowledge, values, and practices, drawing on themes arising from analysis of focus group data: participants felt that they brought limited knowledge of their Indigenous language and culture to their program, and participants experienced an awakening of Indigenous knowledge through their participation in Indigenous practices outside the core curriculum.